Effect of Malic Acid on Growth Performance, Carcass Characteristics, and Feed Efficiency in the Broiler Chickens - Moharrery, A. (International Journal of Poultry Science, 2005)
This study was performed with growing chicken (1 to 56 d of age) to evaluate the effects of malic acid on broiler chicken performance. Malic acid was added to the water and offered to chicken freely from first to end of experiment with constant concentration. The treatments were zero (as a control), 0.05, 0.10, and 0.15 percent of malic acid which dissolved in water and given to them in waterer pan. The effect of treatments was investigated using 192 broiler chickens. The experimental design was a completely randomized with four treatments and four replicates. Each of four replicates was contain 12 pieces of chicken. Corn and soybean based diet were fed in mesh form, and the chickens had free access to diet and water. At the end of trial, two birds (one male and another female which selected phenotypically) from each pen were slaughtered. Blood sample has been taken just before slaughter of birds for serum analyzing. No significant difference (P> 0.05) was observed between treatments for weight gain and feed conversion, but treatment with 0.15% malate showed lowest feed intake (P = 0.0590). Highest water consumption has been observed in water with 0.05% malate concentration. This amount was 3.82% higher than control (P = 0.0769) meanwhile water with 0.15% malate showed lowest water consumption among malic acid treatments. The difference between 0.05 and 0.15 percent of malate was 3.76% for water consumption (P = 0.0811). Reduction of serum cholesterol was observed in birds on 0.05% malate (P< 0.05), meanwhile highest serum glucose was belong to 0.10% malate concentration (P< 0.05). Added malate to the water resulted in differences in liver composition. Chicks given 0.15% added malate had lowest liver dry matter and glycogen, and highest protein (P< 0.05). Result showed significant interaction between treatment and sex for percentage yield of breast (P = 0.0466).